COMMUNICATION OF ONCOLOGICAL PATIENTS WITH ONCOLOGISTS: MAIN PROBLEMS AND PROBLEM-SOLVING STRATEGIES - Zub, V. О.; Kotuza, A. S.; Tolstanov, O. K. (International Journal of Medicine and Medical Research, 2023)
Background. Physician-patient сommunication is one of the main supportive care provided to oncological patients. It affects treatment outcomes, as well as the interaction of patients within the society, their family and colleagues. Furthermore, COVID-19 and military invasion of Russia into Ukraine makes the issue of improvement of physician-patient communication urgent. Objective. The aim of the study is to develop recommendations based on the analysis of denfined problems in physician-patient communication in of oncological treatment. Methods. The sociological research involved 419 patients during their inpatient treatment in the period from November 2021 to February 2022 using the EORTC QLQ-COMU26 questionnaire. Results. In the pre-war period, in Ukrainian patients with oncological diseases the worst indicators were established for “Active role of a patient” (82.00) and “Correction of misunderstandings by a specialist” (89.19). The best indicators were established for “Skills of the specialist (verbal/non-verbal)” with the score of 93.25 by a 100-point grading scale, as well as “Satisfaction with communication” – 97.04 by a 100-point grading scale. Conclusions. When developing programs for organization of oncological care, mechanisms for providing psychological care to patients through effective communication between patients and specialists regarding providing medical and psychological care must be taken into account.